Development of non-conservative mechanical models applied to the low energy impact phenomenon (2018)
Non-conservative mechanical models are developed to be applied to the low energy impact phenomenon. The analytical description of the proposed models is made and the numerical solution of the system of differential equations is proposed. The impact of materials is undoubtedly the object of research, due to the dynamic condition inherent in the bodies that interact in our universe. That is why we have standardized methodologies for its study, such as Izod and Charpy impact techniques, among others. However, this work places special emphasis on the method of plate bending, which, due to its geometric configuration, interprets real impact situations to which some bodies are subjected, in addition to the low energy technique in which the energy available in the impactor is less than that absorbed in the breaking process, makes it possible to obtain information on the material in the elastic, plastic, initiation and crack propagation range.